Unpunished criminals: The social acceptablity of white collar crimes in America - Martinez, Joseph P. (2014)
White collar crime is a serious issue in the United States of America, responsible for an estimated $250 billion to $1 trillion in economic damages each year. White collar crimes include: bank fraud, blackmail, bribery, counterfeiting, credit card fraud, embezzlement, extortion, forgery, insider trading, insurance fraud, investment schemes, securities fraud, tax evasion, advanced fee scams, service and repair scams, as well as Ponzi & pyramid schemes just to name a few. There are a number of factors to consider regarding crimes, both street and white collar level including: the total cost of the damages and ripple effects that will reach others, how likely the victims are to recover from the crime, and how likely the victims are to get justice for being wronged, when considering the acceptability that society has placed on white collar crimes versus street crimes. As seen in case studies, white collar criminals are far less likely to experience justice than street criminals, who are also more likely to be caught in their wrongdoing. Because white collar criminals have this additional safety barrier of anonymity, federal law enforcement must dig deeply into the records of suspected individuals in order to find any trace of white collar criminal activity. Whereas the affluent have access to pricey legal representation for defense against potential repercussions, street criminals cannot retain such legal representation, leaving them considerably more vulnerable in the legal system. Therefore, white collar criminals are seen and treated as more socially acceptable than street criminals in America